Social support of mentally retarded persons - Zwolinska, Danuta; Podstawski, Robert; Nowosielska-Swadzba, Danuta; Jendrysek, Marek (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: The aim of this work is to assess the relationship between the environment and mentally retarded persons. Material and methods: Information referring to social support of mentally retarded persons is a source material collected on the base of the data included in the Polish and foreign literature. The issues under discussion related to the following problems: social integration of persons with intellectual disabilities in a family and local environment, social functioning of people with mild intellectual disability, social rehabilitation of people with moderate, severe and profound intellectual disability and specific contact with people with disabilities. Results: For a person with an intellectual disability, the family is the source of acquisition of basic social skills that give him the opportunity for further development and performing certain social roles in a sense of safety. Full acceptance of the intellectually disabled, may dismiss their sense of shame and fear, and instill the satisfaction of belonging to a social community. Conclusions: Full social acceptance of people with intellectual disabilities is the basis for their assimilation and social functioning.